Preparation and Cytotoxic Evaluation of PGV-1 Derivative, CCA-1.1, as a New Curcumin Analog with Improved-Physicochemical and Pharmacological Properties - Utomo, Rohmad Yudi; Wulandari, Febri; Novitasari, Dhania; Lestari, Beni; Susidarti, Ratna Asmah; Jenie, Riris Istighfari; Kato, Jun-Ya; Sardjiman, Sardjiman; Meiyanto, Edy (Tabriz University of Medical Sciences, 2022)
Purpose: This study aimed to challenge the anticancer potency of pentagamavunone-1 (PGV- 1) and obtain a new compound (Chemoprevention-Curcumin Analog 1.1, CCA-1.1) with improved chemical and pharmacological properties. Methods: CCA-1.1 was prepared by changing the ketone group of PGV-1 into a hydroxyl group with NaBH4 as the reducing agent. The product was purified under preparative layer chromatography and confirmed with HPLC to show about 93 purity. It was tested for its solubility, stability, and cytotoxic activities on several cancer cells. The structure of the product was characterized using 1HNMR, 13C-NMR, FT-IR, and HR-mass spectroscopy. Results: Molecular docking analysis showed that CCA-1.1 performed similar or better interaction to NF-κB pathway-related signaling proteins (HER2, EGFR, IKK, ER-alpha, and ER-beta) and reactive oxygen species (ROS) metabolic enzymes (NQO1, NQO2, GSTP1, AKC1R1, and GLO1) compared with PGV-1, indicating that CCA-1.1 exhibits the same or better anticancer activity than PGV-1. CCA-1.1 also showed better solubility and stability than PGV-1 in aqueous solution at pH 1.0-7.4 under light exposure at room temperature. The cytotoxic activities of CCA-1.1 against several (10) cancer cell lines revealed the same or better potency than PGV-1. Conclusion: In conclusion, CCA-1.1 performs better chemical and anticancer properties than PGV-1 and shows promise as an anticancer agent with high selectivity. © 2022 The Author (s).